Effects of Earthworm (Pheretima communisima) extract on atopic dermatitis: An in vitro and in vivo study - Yoon-Young Sung; Heung-Joo Yuk; Seung-Hyung Kim; Dong-Seon Kim (Heliyon)
Earthworm (Pheretima communisima) is used as a traditional medicine for the management of allergic airway inflammation. Atopic dermatitis (AD) is a persistent, recurrent disorder marked by allergic inflammation and skin barrier dysfunction. However, the pharmaceutical effects of earthworms on AD have not been defined. Our study examined the anti-allergic and anti-inflammatory actions of earthworm ethanolic extract (EWE) on allergic skin inflammation in a Dermatophagoides farinae mite antigen-induced AD mice model, TNF-α/IFN-γ-treated human keratinocytes, and compound 48/80-treated mouse mast cells. Oral administration of EWE in AD mouse reduced inflammatory cell accumulation, epidermal hyperplasia, and dermatitis severity in AD skin lesions and thymic stromal lymphopoietin (TSLP) and immunoglobulin (Ig) E concentrations in serum. EWE administration in AD mice also reduced secretion of Interleukin (IL)-4, IL-13, IL-5, and IFN-γ in cultures of isolated splenic cells. Immunohistofluorescence staining of skin lesions from AD mice revealed that EWE induced expression of claudin-1, filaggrin, and SIRT1. In HaCaT keratinocytes cotreated with IFN-γ and TNF-α, EWE inhibited secretion of the chemokine Regulated on Activation, Normal T Cell Expressed and Secreted (RANTES) in a dose-dependent manner. In addition, EWE inhibited histamine release in activated MC/9 mast cells. These results show that EWE might be therapeutics for the management of AD.